A comunicação institucional em universidades públicas: a perspectiva da administração superior da UFC - Coutinho, Mayra Pontes (2015)
In a globalized world, where information spreads fast, communication plays an important role in all kinds of organizations, including Higher Education Institutions (IES). However, in order to obtain good results, not only the existence of a professional communication sector, but also the involvement of the superior administration from these institutions with the area are fundamental. The leaders must authorize the transformation of communication into an instrument for the qualification of processes and also of organizational identity, also taking part in this process. Based on this panorama and on the observation that little attention is given to the behavior of the leaders of higher education institutions with relation to communication in the academic literature, the goal of this study is to analyze the role of institutional communication under the perspective of the senior management staff at the Federal University of Ceará (UFC). The theoretical review articulated concepts related to integrated communication, to communication management, to strategic communication, among others. In order to reach the established goal, semi-structured interviews with senior management members at UFC were accomplished. Making use of a qualitative approach, the data were transcribed and analyzed according to the method of content analysis. The results indicate that the UFC managers who were interviewed recognize communication as something fundamental in the relationship with different stakeholders, especially for the internal public. According to them, the communication actions are instruments that help in the legal reporting and in transparency, allowing society to know what the work developed by UFC is. But despite the acknowledgment of its importance, for the great majority of the leaders, communication still occupies an instrumental dimension, more related to its role of announcing the decisions made.